Exploring the Impact of Globalization on Project Management: Investigating through the Critical Elements – Definition, Differentiation & Dimensions of Global Project - Shaikh, Mohammed Ovees (2012)
Globalization has had a huge impact on the way businesses are being conducted. It has opened doors for huge opportunities and provided a universal platform to organizations in one end of the world to communicate and conduct business across other end of the world. Globalization has broadened the horizon of organizations and provided opportunities for their strengths and products to be marketed across the world. Nonetheless, despite increased revenues for businesses engaging in global business prospects, there are lot of challenges that the organizations and its work force needs to face in order to manage this cross cultural and global business. The paper researches into the area of Project management and how it is affected in global projects. The research paper emphasis on three key areas, defined as the critical elements, of global projects. The three elements are definition, differentiation and dimensions of global projects. The three areas are deeply researched into through the literature review and analyzed using data collection methods with people and organizations engaged in global projects. The research also looks for variables that define the global-ness of projects and how the implications of managing and planning them change. The research also provides an execution model for global projects from project management perspective. The model is comprised of the author’s own project management methodology that is improved and enhanced based on the literature review and data collected for this research. The research is based in the United Arab Emirates. The author is based in the UAE and works in global project environment for an organization that is very global in its nature. The research builds its foundation with the author’s personal experience in global projects and the growing trend of global projects mainly in the UAE due to its location and its structure of laws and regulations. The UAE served to be an ideal destination for this research since the author’s network and organization is engaged in global projects, similar to a lot of other multinational companies in the country, and majority of work force in the country is comprised of expatriates coming from different parts of the world. The data that is collected for this research is divided into two sets. Set 1 is comprised of Interview questions with project managers involved in a global project. Set 2 is comprised of survey questionnaires with Project team members involved in a global project. The respondents for both sets come from different industries to provide more variance in the results and a broader perspective on the subject. The results of the research, as displayed in the Data Analysis section, suggest a growing trend of global projects in the UAE and there is improvement that is occurring in execution of global projects however, it is not up to the pace with the growth in global projects. Another important point extracted from the data suggests that organizations do not have the right vision when it comes to planning of global projects in terms of investment and enforcement of the right tools and the allocation of right people in global projects. The research looks for relevant topics to global projects across different literature review references coming from authors around the world however; the data that is collected has its roots in the UAE. Hence, further research could be conducted in this area in other countries to verify the trends and the execution models for global projects. The research aims to provide organizations with a view of global projects and their complications which are under estimated. The research also aims to provide a ground work for future research to be conducted in developing models and solutions to managing global projects.